2014
DOI: 10.1371/journal.pone.0086131
|View full text |Cite
|
Sign up to set email alerts
|

Circular Polarization of Transmitted Light by Sapphirinidae Copepods

Abstract: Circularly polarized light, rare in the animal kingdom, has thus far been documented in only a handful of animals. Using a rotating circular polarization (CP) analyzer we detected CP in linearly polarized light transmitted through epipelagic free living Sapphirina metallina copepods. Both left and right handedness of CP was detected, generated from specific organs of the animal's body, especially on the dorsal cephalosome and prosome. Such CP transmittance may be generated by phase retardance either in the mus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Furthermore, complexes of biopolymers, such as arthropod cuticles, plant cell walls and human compact bone osteon, form cholesteric liquid crystals and scatter CPL (Mitov and Dessaud 2006). Studies have suggested that communications in the scarab beetle Chrysina gloriosa involve CPL reflection (Brady and Cummings 2010), and several types of crustaceans, including stomatopods (Chiou et al 2008), sapphirinidae copepods (Baar et al 2014) and mantis shrimp (Gagnon et al 2015), have been reported to recognize CPL. Plant tissues that reflect CPL include Pollia fruit (Vignolini et al 2012), leaves of the herb Mapania caudate (Strout et al 2013) and starch granules from Solanum tuberosum (Zhuo et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, complexes of biopolymers, such as arthropod cuticles, plant cell walls and human compact bone osteon, form cholesteric liquid crystals and scatter CPL (Mitov and Dessaud 2006). Studies have suggested that communications in the scarab beetle Chrysina gloriosa involve CPL reflection (Brady and Cummings 2010), and several types of crustaceans, including stomatopods (Chiou et al 2008), sapphirinidae copepods (Baar et al 2014) and mantis shrimp (Gagnon et al 2015), have been reported to recognize CPL. Plant tissues that reflect CPL include Pollia fruit (Vignolini et al 2012), leaves of the herb Mapania caudate (Strout et al 2013) and starch granules from Solanum tuberosum (Zhuo et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Circularly polarized light is another form of polarized light that is less common in nature (Heinloth et al, 2018). Previous studies have indicated that circularly polarized light is a covert signal in the intraspecific communication of stomatopod crustaceans (Templin et al, 2017), and that it can alter their mating selections (Chiou et al, 2011;Baar et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have revealed that CP light can be perceived by mantis shrimp and that it affects their mating behavior and defensive behaviors (Chiou et al, 2008;Baar et al, 2014;Gagnon et al, 2015;Templin et al, 2017). Michelson (1911) initially reported on reflection of polarized light in some scarab beetles (Michelson, 1911), with subsequent studies revealing that their exocuticle selectively reflects left circularly polarized (LCP) light (Finlayson et al, 2017;Bagge et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…As described above, many species such as fish, cephalopods, crustaceans, and insects, among others, have evolved to perceive polarized vision as a means of navigation, communication, and mate selection. , During this course of evolution, various species have developed structural color using helical architectures. ,,, A distinct feature of the structural color formed from helical structures is the angle-dependent reflection, resulting in a striking iridescence and the selective reflection of single-handed polarized light …”
Section: Optical Materials and Optical Engineering In Biology And Naturementioning
confidence: 99%
“…139,159−161 During this course of evolution, various species have developed structural color using helical architectures. 8,66,162,163 A distinct feature of the structural color formed from helical structures is the angle-dependent reflection, resulting in a striking iridescence and the selective reflection of single-handed polarized light. 67 Beetles exhibit a brilliant iridescence and an angle-dependent "flash light" appearance due to the presence of helical architectures on the exocuticle.…”
Section: Polarized Vision Of Aquatic Organisms Polarizedmentioning
confidence: 99%